2007
DOI: 10.1097/01.ccm.0000257330.54882.be
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and respiratory changes during lung recruitment and descending optimal positive end-expiratory pressure titration in patients with acute respiratory distress syndrome*

Abstract: Following lung recruitment and descending optimal PEEP titration, the Pao2 improves significantly, without any change in the EVLW up to 1 hr. This suggests a decrease in atelectasis as a result of recruitment rather than a reduction of EVLW. There is a significant change in CI during the maneuver, but neither central venous pressure, heart rate, nor MAP can reflect these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 37 publications
(33 reference statements)
2
61
1
4
Order By: Relevance
“…PEEP is then decreased in 2-cm H 2 O decrements, and the compliance is measured at each step to determine best compliance. Others have used arterial oxygenation [25][26][27] or dead space 28 rather than compliance to identify best PEEP during the decremental PEEP titration. After using either compliance or oxygenation to identify the pressure at which recruitment is not maintained, the recruitment maneuver is then repeated, after which PEEP is set 2 cm H 2 O greater than the level identified as best compliance.…”
Section: Types Of Recruitment Maneuversmentioning
confidence: 99%
“…PEEP is then decreased in 2-cm H 2 O decrements, and the compliance is measured at each step to determine best compliance. Others have used arterial oxygenation [25][26][27] or dead space 28 rather than compliance to identify best PEEP during the decremental PEEP titration. After using either compliance or oxygenation to identify the pressure at which recruitment is not maintained, the recruitment maneuver is then repeated, after which PEEP is set 2 cm H 2 O greater than the level identified as best compliance.…”
Section: Types Of Recruitment Maneuversmentioning
confidence: 99%
“…[58][59] No studies have measured the impact of lung recruitment on total lung water volume in children however a study by Toth and colleagues in adults did conclude that improvements in oxygenation post recruitment was independent of redistribution of extravascular lung water. 60 Another study demonstrated a net alveolar fluid clearance post recruitment which the authors attributed to resorption of alveolar oedema. 61 …”
Section: Lung Watermentioning
confidence: 99%
“…Concerns include the potential for barotrauma, pneumothoraces and the possible contributory factor to both VILI and ventilator associated pneumonia (VAP). 12,20,36,44,60 Other concerns include the potential to impact negatively on haemodynamics and intracranial pressure. 17 By increasing the intrathoracic pressure during the recruitment manoeuvre an inevitable consequence is a commiserate reduction in venous return and subsequent cardiac output.…”
Section: What Harm Can Lung Recruitment Cause?mentioning
confidence: 99%
“…En los últimos años, diversos estudios clínicos y experimentales han mostrado la presencia de efectos cardiovasculares asociados a la MR [9][10][11][12][13][14] . El efecto hemodinámico principal encontrado es una disminución significativa del gasto cardíaco durante la realización de la maniobra.…”
Section: Efectos Adversos Durante El Reclutamiento Alveolar Agresivounclassified
“…Este fenómeno habitualmente es reversible en pocos minutos tras la finalización de la maniobra; sin embargo, puede producirse un descenso del gasto cardíaco de gran magnitud. En este sentido, se han observado caídas de hasta un 60% del gasto cardíaco que tuvieron como consecuencia un incremento de los fármacos vasoactivos para lograr la estabilización hemodinámica de los pacientes estudiados 14 . Generalmente, los cambios observados en la presión arterial media son menos pronunciados que el descenso en el gasto cardíaco 13,14 , por lo que la monitorización de la presión arterial subestima los verdaderos efectos cardiovasculares de las MR, los cuales podrían ser detectados a través de la monitorización continua del gasto cardíaco.…”
Section: Efectos Adversos Durante El Reclutamiento Alveolar Agresivounclassified